2016
DOI: 10.4103/2211-4122.183751
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional transesophageal echocardiography demonstration of left atrial appendage echocontrast regression after 6 months therapy with dabigatran and not with warfarin

Abstract: While warfarin therapy is efficacious in treating left atrial (LA) thrombus formation in patients with nonvalvular atrial fibrillation (AF), it does not affect red cell aggregation in vitro or LA spontaneous echo-contrast in patients. In this patient with left ventricular (LV) dysfunction secondary to AF, we observed the disappearance of dense echo-contrast in the atrial appendage after therapy with dabigatran and not with well-controlled warfarin. This allowed us to analyze accurately the appendage with three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In addition to the reduction or disappearance of thrombus in some patients following anticoagulant therapy, we also observed that in some patients with left atrial or LAA spontaneous echo contrast, the spontaneous echo contrast was disappeared or reduced after anticoagulant therapy. Vestito et al [ 14 ] made a comparative study of the effects of dabigatran and Warfarin on spontaneous echo contrast in LAA of patients with AF, and the results showed that the spontaneous echo contrast was disappeared or reduced in LAA of patients with AF after dabigatran anticoagulant therapy, while after Warfarin anticoagulant therapy, there was no significant change in spontaneous echo contrast. Mahony et al [ 15 ] also observed a decrease in the degree of LA spontaneous echo contrast during antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the reduction or disappearance of thrombus in some patients following anticoagulant therapy, we also observed that in some patients with left atrial or LAA spontaneous echo contrast, the spontaneous echo contrast was disappeared or reduced after anticoagulant therapy. Vestito et al [ 14 ] made a comparative study of the effects of dabigatran and Warfarin on spontaneous echo contrast in LAA of patients with AF, and the results showed that the spontaneous echo contrast was disappeared or reduced in LAA of patients with AF after dabigatran anticoagulant therapy, while after Warfarin anticoagulant therapy, there was no significant change in spontaneous echo contrast. Mahony et al [ 15 ] also observed a decrease in the degree of LA spontaneous echo contrast during antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 99%